Perancangan UI Dan UX Aplikasi Pemesanan Buket Menggunakan Metode Double Diamond - Perdana, Dimas Elang; Totohendarto, Moch Hafid; Ma’ruf Nugroho, Imam (STMIK Banjarbaru, 2023)
Business development in Indonesia has been growing, especially the type of bouquet business, one of which is the Desshine Bouquet Store. However, currently Desshine Store does not have any specific activities or strategies that handle marketing and ordering products made. Looking at the problem of Deshhine Store which still uses social media and is not mobile-based. Therefore, a user interface design is needed before designing the application. Certain techniques are needed to design a bouquet ordering user interface that can facilitate the delivery of information and the ordering process for users. This study presents the design of the user interface of the bouquet ordering application using the Double Diamond method and user experience testing using the User Experience Questionnaire (UEQ) method which aims to measure the results of the design of the user interface design. The test results found that three UEQ scales were rated very good